Obstructive Uropathy and Vesicovaginal Fistula Secondary to a Retained Sex Toy in the Vagina. (1st October 2014) - Donaldson, James Fergus; Tait, Campbell; Rad, Marcel; Walker, Shonagh; Lam, Thomas B.L.; Abdel‐Fattah, Mohammed; Swami, Satchi Kuchibhotla
Abstract: Introduction: Vaginal foreign bodies (FBs) are a rare cause of vesicovaginal, rectovaginal, or urethrovaginal fistulae. Aim: The aim of this study was to describe a rare case of vesicovaginal fistula (VVF) and obstructive uropathy and to review the literature. Methods: A case is presented. A comprehensive review of the literature was performed (1948–2013). Results: A 38‐year‐old woman presenting with sepsis, obstructive uropathy, and severe emaciation was found to have a sex toy retained in her vagina for 10 years. This had caused a VVF and bilateral hydroureteronephrosis. Bilateral nephrostomies were inserted and she underwent cystoscopy and examination under anesthesia (EUA) with retrieval of FB. A left ureteric stricture was demonstrated. Transabdominal VVF repair with omental flap and left ureteric re‐implantation was performed. The VVF recurred, which was successfully re‐repaired transvaginally. Seventy‐six full text articles were reviewed. There were no previously published cases of VVF following vaginal sex toy insertion. There are four cases of obstructive uropathy secondary to a vaginal FB in the literature: three pessaries and one plastic cap. There are 44 cases of VVF secondary to FB: 22 plastic caps (typically from aerosol bottles, inserted for masturbation or contraception) and 5 pessaries. At least nine were in girls aged ≤18 years. Average presentation is 15 months (range 2 months to 35 years) after FB insertion. Most cases were managed with surgical repair; predominantly transvaginal. Conclusions: This case describes an extremely rare but potentially life‐threatening case of obstructive uropathy caused by a chronically retained sex toy, and adds to the list of potentially rare causes of a VVF and obstructive uropathy. We advocate urinary diversion, staged removal of FB, upper urinary tract imaging, and EUA with VVF repair and/or ureteric reimplantation if required. Transvaginal is the preferred access for FB‐associated VVF repair without concomitant ureteric reimplantation.